(untitled) (Metallurgy and Foundry Engineering, 2012)
An attempt of water glass modifying by 30% water bochmite Al(OH)O solution was undertaken. The flow curves were determined and the binder viscosity estimated from them. The quartz wettability by binders was determined by measuring the wetting angle θ changes with time. Strength properties of moulding sands with fractions of modified binders were verified by checking the tensile strength [formula] after various hardening times under environmental conditions. The [formula] value after 24 h of hardening was assumed for the analysis.